Investigation on mechanochemical behavior of the TiO2–Mg–C system reactive mixtures in the synthesis of titanium carbide. (September 2015) - Ebrahimi-Kahrizsangi, Reza; Alimardani, Marzieh; Torabi, Omid
Abstract: TiC–MgO composite was synthesized using mixtures of TiO2, Mg, and wood dust via a mechanochemical process. The influence of various Mg values (0–2.4 mol) on the titanium carbide formation and the mechanism of reactions during the milling of TiO2 –Mg–C mixture were investigated. Phase transformations, grain size, strain, lattice parameters, and morphology of the powders during the milling process were examined using X-ray diffractometry (XRD) and scanning electron microscopy (SEM). Thermodynamic calculations revealed that the Mg value played a main role. Consequently, the overall reaction enthalpy and adiabatic temperature ( Tad ) changed with variation of the magnesium content. Experimentally, after 10 h of milling, TiC was synthesized in the mixture powder with stoichiometric ratio (Mg = 2 mol). The type of reactions was mechanically induced self-sustaining reaction (MSR). In addition, at lower Mg content (Mg = 1.5), the heat resulted from magnesiothermic reaction also activated the carbothermal reduction. Further decrease in the Mg value (Mg = 0.5 and 1 mol) resulted in formation of MgTiO3 as a major phase. Using the excess Mg value (Mg = 2.2 and 2.4 mol Mg) as a diluent agent led to formation of Mg2 TiO4 besides the MgO and TiC phases. Highlights: Mg content plays a key role in the mechanochemical behavior of Mg–TiO2 –C. By increasing milling time, an exothermic reaction occurs before magnesium melting. Magnesiothermic reaction provided enough heat for activating carbothermic reaction. Mg, within a range of 1.5–2.2 mol promoted a self-sustaining reaction.